2012
DOI: 10.1111/j.1439-0272.2012.01301.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of 4-hourly ejaculates - levels of calcium and magnesium

Abstract: IntroDuCtIon Artificial insemination is one of the methods widely used in the treatment of male infertility [1-4]. Many childless couples prefer homologous artificial insemination in which a portion of split ejaculate containing rich and active spermatozoa was shown to give good results in such cases [5-8]. Furthermore, in cases of oli-gospermia it was the preferred choice. These outcomes prompted spilt ejaculation studies in order to understand semen details and the origin of each component in semen [9-12] Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 40 publications
0
15
0
2
Order By: Relevance
“…Several studies have suggested extremely short EA lengths (i.e. <1–4 h) due to their positive influence on semen parameters (Gosalvez et al ., ; Valsa et al ., ; Bahadur et al ., ; Mayorga‐Torres et al ., ; Ayad et al ., ). A recent systematic review of 28 studies suggested that longer EA is associated with increased semen volume and sperm count, which is also in agreement with our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have suggested extremely short EA lengths (i.e. <1–4 h) due to their positive influence on semen parameters (Gosalvez et al ., ; Valsa et al ., ; Bahadur et al ., ; Mayorga‐Torres et al ., ; Ayad et al ., ). A recent systematic review of 28 studies suggested that longer EA is associated with increased semen volume and sperm count, which is also in agreement with our findings.…”
Section: Discussionmentioning
confidence: 98%
“…Frequency of collection was having a significant effect on the composition of semen, with respect to volume, sperm density, seminal plasma constituents and other parameters. 25,26,[29][30][31][32] Mode of collection of sample was masturbation. Coitus interruptus was not advised due to chances of losing one or two drops during collection as well as mixing the sample with vaginal secretions and vaginal cells.…”
Section: Discussionmentioning
confidence: 99%
“…Calcium and magnesium content in human semen has been reported previously [10, 11, 13, 14]. Calcium is essential for sperm motility [3642], metabolic functions [44], acrosome reaction, and fertilization [38, 41, 44, 45].…”
Section: Discussionmentioning
confidence: 99%